Melting Phase Relations and Element Partitioning in MORB to Lowermost Mantle Conditions. Issue 7 (17th July 2018) - Tateno, Shigehiko; Hirose, Kei; Sakata, Shuhei; Yonemitsu, Kyoko; Ozawa, Haruka; Hirata, Takafumi; Hirao, Naohisa; Ohishi, Yasuo
Abstract: Melting phase relations and crystal‐melt element partitioning in a mid‐oceanic ridge basalt bulk composition were studied to 135 GPa using laser‐heated diamond‐anvil cell techniques. Using field‐emission‐type electron microprobe (FE‐EPMA), transmission electron microscope (TEM), and laser ablation‐inductively‐coupled plasma mass spectrometer (LA‐ICP‐MS), we obtained comprehensive analyses of major and trace elements in coexisting melt and solid phases. CaSiO3 ‐perovskite (Ca‐pv) was found to be the liquidus phase throughout the lower mantle pressure range. Whereas silica, followed by Mg‐perovskite, are the second and third crystallizing phases to pressures exceeding 100 GPa, postperovskite, closely followed by seifertite, succeed Ca‐pv at 135 GPa. The partitioning of trace elements between Ca‐pv and melts exhibited a strong pressure effect, possibly due to a combination of high compressibility of cations compared to the lattice site in Ca‐pv and melt compressional effects. The Ca‐pv/melt partition coefficients for Na and K ( D Na and D K ) increase with increasing pressure, with D Na close to unity and D K greater than unity at lowermost mantle pressures. Also, D Nd becomes larger (or identical within uncertainty) than D Sm in the deep lower mantle. Partial melt formed by 51% partial melting of mid‐oceanic ridge basalt at 135 GPa showed marked iron‐enrichment and should thus have negative buoyancy at the base of the mantle. The density of residual solid is almost identical to the PREM density, and therefore, it is likely to be involved in mantle convection and recycled to the surface. Key Points: Melting relations and element partitioning in MORB have been studied comprehensively by EPMA, TEM, LA‐ICP‐MS, and XRD to the CMB pressure Iron‐rich partial melts form from MORB materials at the base of the mantle, whose liquidus phase is Ca‐perovskite Strong pressure effect on Ca‐pv/melt element partitioning due to higher compressibility of large cations compared to a crystal lattice site